Influence of the impurities in the hybrid discharges with high power in JET ILW. (1st June 2022) - Ivanova-Stanik, I.; Challis, C.D.; Chomiczewska, A.; Hobirk, J.; Huber, A.; Kappatou, A.; Lerche, E.; Telesca, G.; Zagórski, R.; JET Contributors,
Abstract: The aim of this paper is to numerically study the influences of the impurities on the high power hybrid discharges in the JET ITER-like wall (ILW) configuration in the DD and deuterium–tritium (DT) scenarios. Numerical simulations with the COREDIV code of hybrid discharges with 32 MW auxiliary heating, 2.2 MA plasma current and 2.8 T toroidal magnetic field in the ILW corner configuration are presented. In the simulations five impurity species are used: intrinsic: beryllium (Be) and nickel (Ni) from the side walls, helium (He) from DT reaction, tungsten (W) from divertor and extrinsic neon (Ne) or argon (Ar) by gas puff. The extrapolation of the DD discharges to DT plasmas at the original input power of 32 MW and taking into account only the thermal component of the alpha-power, does not show any significant difference regarding the power to the target with respect to the DD case. Simulations show that sputtering due to D and T is negligible. In contrast, the simulations at auxiliary heating 39 MW show that the power to the target is possibly too high to be sustained for about 5 s by strike-point sweeping alone without any control by Ne seeding. The tungsten is produced mainly by Ni, Be and seeded impurities.